National fertilizer supply and supply adjustment planning in Bangladesh - Samad, A. (International Food Policy Research Institute, 1987)
The use of chemical fertilizers in crop production is a comparatively recent practice in Bangladesh. In 1951/52, the earliest year for which any data are available, about 10,000 tons of ammonium sulfate were used, almost entirely on tea gardens; use of chemical fertilizers by ordinary farmers was practically unknown. Records indicate that in 1949/50, the government drew up a scheme to distribute annually for five years about 24,000 tons of ammonium sulfate, 18,000 tons of oil cakes, 15,000 tons of lime, 30,000 tons of bonemeal and superphosphate, and 7,000 tons of seed for green manure crops. Progress was insignificant because of farmers' ignorance about the benefits of fertilizer use, lack of a vigorous promotion effort by the government, and almost total absence of a marketing infrastructure. Though some progress was made during the 1955-60 Five-Year Plan under the Grow-More-Food campaign, fertilizer consumption was no more than 50,000 tons in 1959/60.